(untitled) (The Journal of Plant Protection Sciences, 2020)
Comparative efficacy of penoxsulum 24 SC against weeds in transplanted kharif rice was studied atRegional Research Sub-Station (New Alluvial Zone), Bidhan Chandra Krishi Viswavidyalaya,Chakdaha, Nadia, West Bengal. The experiment was laid out in a randomized block design with 7treatments and 3 replications. The results revealed that the major weed flora associated with the transplanted rice during kharif season was mainly comprised of Echinochloa colona (30 %), Cyperusdifformis (20 %), Monochoria vaginalis (30 %) and Ludwigia parviflora (20 %). Penoxsulam 24 SCat 0.0225 kg a.i. ha-1 applied at 8-12 days after transplanting was most effective to check all types ofweed population and their growth. This treatment also gave the maximum grain yield (3.53 tha-1) andstraw yield (4.73 tha-1) of rice resulting in lowest weed index (5.61 %). Therefore,